Attitude and Practice towards Pre-exposure Prophylaxis (PrEP) for HIV Prevention among Female Sex Workers in Kicukiro District, Rwanda - Umulisa, Alice; Urayeneza, Dr Yves; Hategekimana, Viateur (Indonesian Academy of Social and Religious Research (IASRR), 2024)
This study aimed to assess the attitude, and Practice of female sex workers towards Pre-exposure Prophylaxis for HIV prevention in the Kicukiro district, Rwanda. The study used a descriptive cross-sectional design, using a probability sampling method, and the Yamane formula was used to calculate the sample size of 300 female sex workers including a 10% non-response rate. Primary data was collected using a structured questionnaire, at 10 health centers. Analysis was conducted using IBM SPSS software, with chi-square tests and logistic regression for inferential analysis. The ethical clearance was acquired from the Mount Kenya University ethics committee and the Young Women Christian Association Rwanda. The study findings showed that (60%) of female sex workers have a positive attitude towards PrEP, and 60.4% of respondents were using PrEP. Demographic factors like age group, marital status, and Ubudehe category were significantly associated with practices. Female sex workers aged between 25 and 29 had 4 times more chance to have good practices. This study provides insights into improving PrEP education and interventions targeting female sex workers and other key populations. These findings highlighted the concerns about stigma and privacy, and the need for public health interventions that target it in the community.